(3TQM GdSeQbfOis - (3Gdedhi TgGH GdOjf CMeOs; (3GdSeQbfOjs
(3ChdgG (B:s
(3GdMeO ddg GdPi dg GdMeO MbjbI hgh dZjQg eLGR CeG HYO abO cfJ TQMJ QSGdI GdEeGe GdSeQbfOi ai GdGSJYGQGJ hhTMJgG HdWGFa GdWQGFa Ke Ef HYV GdENhGf SCdfi Cf GUQa GdgeI fMh ENJUGQg s
(3BNQgG (B:s
(3aEPG bdJ (B: (3QCjJ CSOkG TGci GdSdGM jQei , aGdTGci GdSdGe CcKQ edGHSI ddQLd YGOI ef GdQei (B( (3adjLYd (B) (3TGci GdSdGM bQjfI hGdQei JLQjO hGddg SHMGfg hJYGdi CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdHdGZIs